GnRH agonist pre-treatment for microwave endometrial ablation in women with less than 1 centimetre myometrial thickness. (17th November 2018) - Nakamura, Kohei; Nakayama, Kentaro; Ishikawa, Masako; Katagiri, Atsuko; Katagiri, Hiroshi; Ishibashi, Tomoka; Sato, Emi; Kyo, Satoru
Abstract: We evaluated the efficacy of gonadotropin-releasing hormone agonist (GnRHa) therapy for improving the myometrial thickness in women with thin (less than 1 cm) uterine walls, a contraindication for microwave endometrial ablation (MEA). The normal myometrium thickness was 0.5 cm, 0.7 cm and 0.9 cm. After the third GnRHa dose, the myometrial thickness increased to over 1 cm in all the three patients, and all were able to undergo MEA. The VAS score for menorrhagia improved in all the cases. The patient satisfaction levels were 10 in 2 of the 3 patients, and 5 in the other. There was no symptom recurrence, and no adjuvant therapy was administered. GnRHa therapy in women with submucous leiomyomata and a myometrial thickness of less than 1 cm could effectively thicken the myometrium, allowing for the use of MEA.